Planning and Mainstreaming Adaptation to Climate Change in Fiscal Policy - Massetti, Emanuele (Staff Climate Notes; Staff Climate Note ;, 2022)
This Staff Climate Note is part of a series of three Notes (IMF Staff Climate Note 2022/001, 2022/002, and 2022/003) that discuss fiscal policies for climate change adaptation. A first Note (Bellon and Massetti 2022, henceforth Note 1) examines the economic principles that can guide the integration of climate change adaptation into fiscal policy. It argues that climate change adaptation should be part of a holistic, sustainable, and equitable development strategy. To maximize the impact of scarce resources, governments need to prioritize among all development programs, including but not limited to adaptation. To this end, they can use cost-benefit analysis while ensuring that the decision-making process reflects society's preferences about equity and uncertainty. A second Note (Aligishiev, Bellon, and Massetti. 2022, henceforth Note 2) discusses the macro-fiscal implications of climate change adaptation. It reviews evidence on the effectiveness of adaptation at reducing climate change damages, on residual risks, and on adaptation investment needs, and suggests ways to integrate climate risks and adaptation costs into national macro-fiscal frameworks with the goal of guiding fiscal policy. It stresses that lower-income vulnerable countries, which have typically not contributed much to climate change, face exacerbated challenges that warrant increased international support. This third Note considers how to translate adaptation principles and estimates of climate impacts into effective policies.